Improving the Skills of the Children of Central Singapadu Village through Balaganjur and Gong Kebyar Training | Meningkatkan Keterampilan Anak-Anak Desa Singapadu Tengah Melalui Pelatihan Balaganjur dan Gong Kebyar - I Wayan Ardinatha Yasa (GHURNITA: Jurnal Seni Karawitan, 2023)
Thematic Real Work Lecture (KKNT) is one of the programs from MBKM (Merdeka Belajar Kampus Merdeka). This KKNT activity is part of the campus extracurricular, which applies the principles of the Tri Dharma of higher education. In this case, KKNT is a bridge in practice that the author carries out in Singapadu Tengah Village, Gianyar Regency, as a partner to add experience to honing community skills and provide motivation and innovation in society in the field of arts, especially in the field of musical arts for generations of young people by forming, fostering crazy percussion on Gong Kebyar and Balaganjur. Balaganjur comes from the words "Bala" and "Ganjur". Bala means troops or ranks, and Ganjur means walking. So, Balaganjur, which later became Balaganjur, means an army or marching line accompanied by barungan gamelan music. Balaganjur is a musical ensemble that is a development of Gamelan Bonang or Bebonangan—both in terms of instruments and the composition of the songs. Gamelan Gong Kebyar is a traditional Balinese musical art in its history written in babad Bali; Gong Kebyar is thought to have appeared in Singaraja in 1915. The village mentioned as the origin of the appearance of Gong Kebyar is Jagaraga (Buleleng), which also started the Kebyar Dance tradition.